Contexts of children’s well-being. Integrating urban development by the municipal smallscale monitoring instrument UWE - Petermann, Sören; Strohmeier, Klaus Peter; Yaltzis, Katharina (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
This article presents results of a pilot-study, which developed a monitoring-instrument for measuring well-being of children and young people in a municipal permanent observation and as evaluation tool. Integrated urban development faces the challenge to absorb negative consequences at the development of children by residential and educational segregation. At the same time, in cities there is a lack of systematic available small-scale data about children in the middle years. The instrument uses human resources as necessary potential for society and measures areas of children’s development strongly linked to well-being and the influence by the socio-spatial contexts: family, school and living environment. A simultaneous testing of these contexts allows options of intervention, which can be used resource-specific.